2021
DOI: 10.3390/biomedicines9080975
|View full text |Cite
|
Sign up to set email alerts
|

Metronidazole- and Amoxicillin-Loaded PLGA and PCL Nanofibers as Potential Drug Delivery Systems for the Treatment of Periodontitis: In Vitro and In Vivo Evaluations

Abstract: The purpose of this study was to prepare poly (D-L) lactide-co-glycolide (PLGA) and poly ε-caprolactone (PCL) nanofibers containing metronidazole and amoxicillin using an electrospinning process as intrapocket sustained-release drug delivery systems for the treatment of periodontal diseases. Scanning electron microscopy showed that the drug containing PLGA and PCL nanofibers produced from the electrospinning process was uniform and bead-free in morphology. The obtained nanofibers had a strong structure and res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 41 publications
2
20
0
Order By: Relevance
“…Moreover, Mirzaeei et al also fabricated PCL nanofibers containing metronidazole and amoxicillin for the treatment of periodontitis. Scanning electron microscopy showed that the drugs containing PCL nanofibers was uniform and bead-free in morphology with the mean fiber diameter as 282 ± 68 nm [ 26 ]. Likewise, the bead-on-string structure was more prominent when sesamin concentration was increased without any alteration of fiber diameter.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, Mirzaeei et al also fabricated PCL nanofibers containing metronidazole and amoxicillin for the treatment of periodontitis. Scanning electron microscopy showed that the drugs containing PCL nanofibers was uniform and bead-free in morphology with the mean fiber diameter as 282 ± 68 nm [ 26 ]. Likewise, the bead-on-string structure was more prominent when sesamin concentration was increased without any alteration of fiber diameter.…”
Section: Resultsmentioning
confidence: 99%
“…41 A recent study suggested the use of polymeric nanofibers loaded with antibiotic combination for targeting gram-negative and gram-positive bacteria as a potential treatment strategy for periodontitis. 42 Based on the antibacterial results, GG3 film was considered to be an optimized formulation for further testing. For the purpose of comparison, blank (B), D1, and O3 films were also subjected to various characterizations.…”
Section: Resultsmentioning
confidence: 99%
“… 41 A recent study suggested the use of polymeric nanofibers loaded with antibiotic combination for targeting gram-negative and gram-positive bacteria as a potential treatment strategy for periodontitis. 42 …”
Section: Resultsmentioning
confidence: 99%
“…The cell culture medium was prepared by immersing 3 mg different samples in a 1 mL commercialized cell culture medium for 24 h at 37 °C, respectively (Mirzaeei et al., 2021 ). The L929 cells were seeded at a density of 1 × 10 4 cells/well in a 96-well plate and cultured for 24 h. Experiments were initiated by replacing the commercial culture medium in each well with 100 µL of sample-prepared culture medium and incubated at 37 °C in a CO 2 incubator.…”
Section: Methodsmentioning
confidence: 99%